PERANCANGAN SISTEM INFORMASI KECAMATAN PRACIMANTORO BERBASIS WEB - Wahyu Tri Putra; Wasino Wasino (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Pracimantoro is a sub-districts located in districts wonogiri and directly adjacent to the Special Region of Yogyakarta, Central Java. Pracimantoro until now has not had an official website, so that people had trouble getting information related Pracimantoro. The goal made a website for the public to obtain information related to Pracimantoro and facilitate Pracimantoro for overall information dissemination to the wider community. Key words        Kecamatan, Pracimantoro, Website, Wonogiri